Analisis Daerah Rawan Kecelakaan Pada Ruas Jalan Tol Becakayu Menggunakan Metode Equivalent Accident Number (EAN) - Tresna Aji, Enggar Aprilia; Firdaus, Rehan; Sanggalangi, Christiyanto; Irfani, Muhammad Rifqi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2024)
The construction of the Becakayu toll road was intended to overcome the issue of traffic congestion by providing a connector between Bekasi and Jakarta. However, as the number of vehicles using this toll road continues to grow, there is a possibility of an increase in accidents. The data from 2019 to 2023 indicates that the number of accidents has increased every year, with 25 accidents resulting in 11 minor injuries reported in 2023. Therefore, it is crucial to analyze the accident prone area to map and reduce the risk of accidents. This study aims to identify the accident-prone areas on the Becakayu toll road using the Equivalent Accident Number (EAN) and Upper Control Limit (UCL) methods. The results indicate that the areas prone to accidents are at KM 10 on track A, and at KM 7 and 8 on track B.